A Study on Dynamic Characteristics of Satellite Antenna System considering 3D Revolute Clearance Joint. (28th August 2020) - Bai, Zhengfeng; Zhao, Jijun
Abstract : Clearances in the joints of real mechanisms are unavoidable due to assemblage, manufacturing errors, and wear. The dual-axis driving and positioning mechanism is one kind of space actuating mechanism for satellite antenna to implement precise guidance and positioning. However, in dynamics analysis and control of the satellite antenna system, it is usually assumed that the revolute joint in the satellite antenna system is perfect without clearances or imperfect with planar radial clearance. However, the axial clearance in an imperfect revolute joint is always ignored. In this work, the revolute joint is considered as a 3D spatial clearance joint with both the radial and axial clearances. A methodology for modeling the 3D revolute joint with clearances and its application in satellite antenna system is presented. The dynamics modeling and analysis of the satellite antenna system are investigated considering the 3D revolute clearance joint. Firstly, the mathematical model of the 3D revolute clearance joint is established, and the definitions of the radial and axial clearance are presented. Then, the potential contact modes, contact conditions, and contact detection of the 3D revolute clearance joint are analyzed. Further, the normal and tangential contact force models are established to describe the contact phenomenon and determine the contact forces in the 3D revolute clearance joint. Finally, a satellite antenna system considering the 3D revolute clearance joint with spatial motion is presented as the application example. Different case studies are presented to discuss the effects of the 3D revolute clearance joint. The results indicate that the 3D revolute clearance joint will lead to more severe effects on the dynamic characteristics of the satellite antenna system. Therefore, the effects of axial clearance on the satellite antenna system cannot be ignored in dynamics analysis and design of the satellite antenna system.